1991
DOI: 10.1172/jci115204
|View full text |Cite
|
Sign up to set email alerts
|

Marked longevity of human lung parenchymal elastic fibers deduced from prevalence of D-aspartate and nuclear weapons-related radiocarbon.

Abstract: Normal structure and function of the lung parenchyma depend upon elastic fibers. Amorphous elastin is biochemically stable in vitro, and may provide a metabolically stable structural framework for the lung parenchyma. To test the metabolic stability of elastin in the normal human lung parenchyma, we have (a) estimated the time elapsed since the synthesis of the protein through measurement of aspartic acid racemization and (b) modeled the elastin turnover through'measurement ofthe prevalence of nuclear weapons-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
381
1
8

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(396 citation statements)
references
References 52 publications
6
381
1
8
Order By: Relevance
“…Modifications in the levels and ratios of these proteins (among others) thus alter relative contributions of each molecule to ECM stiffness. Homeostatic turnover of these proteins is markedly different, with collagen fibers estimated to undergo remodeling at a rate of 3 to 10% per day (25), whereas elastin fibers are long lived, with a mean stability of 74 years in humans (26). In disease, these rates likely vary, although data are sparse in humans.…”
Section: Modulation Of Ecm Stiffnessmentioning
confidence: 99%
“…Modifications in the levels and ratios of these proteins (among others) thus alter relative contributions of each molecule to ECM stiffness. Homeostatic turnover of these proteins is markedly different, with collagen fibers estimated to undergo remodeling at a rate of 3 to 10% per day (25), whereas elastin fibers are long lived, with a mean stability of 74 years in humans (26). In disease, these rates likely vary, although data are sparse in humans.…”
Section: Modulation Of Ecm Stiffnessmentioning
confidence: 99%
“…AAR studies in humans indicate that aortic elastin is much more metabolically stable than the fibrillar collagens (Powell et al 1992) and that elastin in skin, although not replaced, may undergo age-related damage (Ritz-Timme et al 2003). The most compelling evidence for elastic fibre longevity in a human tissue was presented by Shapiro and coworkers (Shapiro et al 1991). Using AAR techniques in combination with mass-spectrometry to assess incorporation of 14 C into both the elastin and glycoprotein (fibrillin microfibril) fractions, this study demonstrated that the age of elastic fibres in the lung corresponded to the age of the individual.…”
Section: Structure and Functionmentioning
confidence: 99%
“…This bound calcium may also play a role in mediating the uptake of lipids by elastic fibres in the ageing arterial wall (for a review see Robert et al 2008). In addition to binding extracellular ions and biomolecules, L-forms of aspartic acid within elastic fibre proteins spontaneously convert to D-forms at a predictable rate (Shapiro et al 1991). Both elastin and fibrillin accumulate D-aspartic acid by aspartic acid racemization, but the consequences for the structure and function of the ageing elastic fibre remain poorly defined (Bailey 2001).…”
Section: Degradationmentioning
confidence: 99%
“…These layers of elastin are essential for the normal compliance of the aorta, allowing it to accommodate the high volume of blood during systole and the elastic recoil during diastole, which maintains an even forward flow of blood to the body against a closed aortic valve. Elastin has a very low turnover because its half-life is ~40 y (30), and the number of elastin lamellar units in a particular vascular segment does not change after birth.…”
Section: Aortic Structure and Compositionmentioning
confidence: 99%